Licensing microgels prolong the immunomodulatory phenotype of mesenchymal stromal cells - Patrick, Matthew D.; Annamalai, Ramkumar T. (Frontiers in Immunology, 2022)
Mesenchymal stromal cells (MSC) are sensors of inflammation, and they exert immunomodulatory properties through the secretion of cytokines and exosomes and direct cell-cell interactions. MSC are routinely used in clinical trials and effectively resolve inflammatory conditions. Nevertheless, inconsistent clinical outcomes necessitate the need for more robust therapeutic phenotypes. The immunomodulatory properties of MSC can be enhanced and protracted by priming (aka licensing) them with IFNγ and TNFα. Yet these enhanced properties rapidly diminish, and prolonged stimulation could tolerize their response. Hence a balanced approach is needed to enhance the therapeutic potential of the MSC for consistent clinical performance. Here, we investigated the concentration-dependent effects of IFNγ and TNFα and developed gelatin-based microgels to sustain a licensed MSC phenotype. We show that IFNγ treatment is more beneficial than TNFα in promoting an immunomodulatory MSC phenotype. We also show that the microgels possess integrin-binding sites to support adipose tissue-derived MSC (AD-MSC) attachment and a net positive charge to sequester the licensing cytokines electrostatically. Microgels are enzymatically degradable, and the rate is dependent on the enzyme concentration and matrix density. Our studies show that one milligram of microgels by dry mass can sequester up to 641 ± 81 ng of IFNγ. Upon enzymatic degradation, microgels exhibited a sustained release of IFNγ that linearly correlated with their degradation rate. The AD-MSC cultured on the IFNγ sequestered microgels displayed efficient licensing potential comparable to or exceeding the effects of bolus IFNγ treatment. When cultured with proinflammatory M1-like macrophages, the AD-MSC-seeded on licensing microgel showed an enhanced immunomodulatory potential compared to untreated AD-MSC and AD-MSC treated with bolus IFNγ treatment. Specifically, the AD-MSC seeded on licensing microgels significantly upregulated Arg1, Mrc1, and Igf1, and downregulated Tnfα in M1-like macrophages compared to other treatment conditions. These licensing microgels are a potent immunomodulatory approach that shows substantial promise in elevating the efficacy of current MSC therapies and may find utility in treating chronic inflammatory conditions.